1987
DOI: 10.1530/jrf.0.0810599
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine changes before and after weaning in response to boar exposure and altered suckling in sows

Abstract: Eighteen sows (6 primiparous and 12 multiparous) were allotted randomly within parity to two lactational treatments: litter separation (LS; 6 h/day) plus boar exposure (BE; 1 h/day; N = 14) beginning 8 days before weaning (4 weeks) and no LS + no BE (controls; N = 4). Blood was collected from all sows via indwelling venous catheters at 20-min intervals for 5 h on Days -1, 0, 1, 2 and 3 from start of treatment. Control sows and those exposed to LS + BE not exhibiting oestrus during lactation were resampled on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Our data do not show any effect of these body reserves on any characteristics of gonadotrophin feedback exerted by the ovaries on the pituitary release of LH and FSH. Similarly, lower FSH concentrations were observed in lactating sows with higher plasma oestradiol [26] as well as negative correlations between plasma FSH measured during lactation or within 48 hours after weaning and follicular characteristics (diameter of 10 biggest follicles, follicular fluid oestradiol, aromatase activity) measured 48 hours after weaning [12]. In addition, negative relationships between plasma oestradiol and inhibin on the one hand and plasma FSH on the other hand were observed on the days after weaning [38].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our data do not show any effect of these body reserves on any characteristics of gonadotrophin feedback exerted by the ovaries on the pituitary release of LH and FSH. Similarly, lower FSH concentrations were observed in lactating sows with higher plasma oestradiol [26] as well as negative correlations between plasma FSH measured during lactation or within 48 hours after weaning and follicular characteristics (diameter of 10 biggest follicles, follicular fluid oestradiol, aromatase activity) measured 48 hours after weaning [12]. In addition, negative relationships between plasma oestradiol and inhibin on the one hand and plasma FSH on the other hand were observed on the days after weaning [38].…”
Section: Discussionmentioning
confidence: 73%
“…The co-enzyme NADPH is necessary for the biosynthesis of fatty acids and, in the pig, MENZ and G6PDH are recognised to be the main enzymes that supply NADPH [43]. Activities of both enzymes were lower in the fat tissues of our lactating sows than in growing pigs [26]. In dairy cows, G6PDH and MENZ activities of the adipose tissue are also very low at the beginning of lactation (week 3) to save glucose and to favour the supply of fatty acids and energy to the mammary glands [6].…”
Section: Discussionmentioning
confidence: 73%
“…Seasonal infertility is caused by a decrease in melatonin and elevated temperatures that occur during summer and thereby inducing a suppression of lactation feed intake, LH release and ovarian follicle growth (Peltoniemi et al, 1999;Ramírez et al, 2009). It is, therefore, reasonable to suggest that the lack of lactation oestrus expression in the fourth replicate was due to seasonally induced suppression of LH release and ovarian follicle growth, as well as a reduced capacity to produce the endocrine response to boar stimuli required for ovulation; a theory supported by Newton et al (1987). The reduced capacity of sows to express a lactation oestrus during the seasonal infertility period emphasises the need to conduct further work in this area to develop strategies to overcome this issue if lactation oestrus management systems are to be commercially viable.…”
Section: Discussionmentioning
confidence: 99%
“…However, suckling induced inhibition of gonadotrophins is reduced as lactation progresses making it possible for sows to be mated prior to weaning, as long as a positive stimulus for LH release is provided (Rowlinson and Bryant, 1982;Varley and Foxcroft, 1990). A number of studies have reported lactation oestrus in the sow in response to boar exposure, split weaning, intermittent suckling, and exogenous gonadotrophins (Guthrie et al, 1978;Newton et al, 1987;Gerritsen et al, 2008a;Zak et al, 2008;Terry et al, 2013). It has recently been demonstrated that providing lactating sows with fence-line exposure with a mature boar, coupled with split weaning, from day 18 of lactation onwards will stimulate a high proportion of sows to express oestrus, and ovulate during lactation .…”
Section: Introductionmentioning
confidence: 99%
“…When separation of sow and piglets is repeated daily [limited nursing or Intermittent Suckling (IS)], lactational oestrus can be induced (Stevenson et al. 1981; Stevenson and Davis 1984; Newton et al. 1987a,b).…”
Section: Introductionmentioning
confidence: 99%